The Prevalence and Factors Associated with Trypanosoma evansi Infection in Beef Cattle of Thapra Livestock Research and Breeding Center - Jaidee, Gantida; Somvech, Thapanee; Saiyasombut, Sirintra (Journal of Mahanakorn Veterinary Medicine, 2023)
The objective of this study is to determine the prevalence and factors associated with Trypanosoma evansi infection in beef cattle of Thapra livestock research and breeding center. The blood samples were collected from 274 cattle between 5th to 7th January 2021. Blood parasites were examined by Haematocrit centrifugation technique (Woo’s technique) and Thin blood smear with Giemsa stain. The results revealed that prevalence of Trypanosoma evansi was 7.66% (21/274). The factors which significantly associated with Trypanosoma evansi were breeds, ages and packed cell volume (P<0.05). Kabinburi’s breed cattle was found 10.69 times of Trypanosoma evansi infection when compared with Sahiwal and Brahman’s breed cattle. Cattle with more than 2 years old was found 7.43 times of Trypanosoma evansi infection when compared with less than or equal to 2 years old. Cattle with packed cell volume under 24% was found 2.93 times of Trypanosoma evansi infection when compared with cattle with packed cell volume more than or equal to 24%. Therefore, it should be concerned over Kabinburi’s breed cattle, cattle with more than 2 years old and cattle with packed cell volume under 24% in order to prevent Trypanosoma evansi infection.